KASPAR – A Minimally Expressive Humanoid Robot for Human–Robot Interaction Research. Issue 3 (25th November 2009) - Dautenhahn, Kerstin; Nehaniv, Chrystopher L.; Walters, Michael L.; Robins, Ben; Kose-Bagci, Hatice; Mirza, N. Assif; Blow, Mike
Abstract : This paper provides a comprehensive introduction to the design of the minimally expressive robot KASPAR, which is particularly suitable for human–robot interaction studies. A low-cost design with off-the-shelf components has been used in a novel design inspired from a multi-disciplinary viewpoint, including comics design and Japanese Noh theatre. The design rationale of the robot and its technical features are described in detail. Three research studies will be presented that have been using KASPAR extensively. Firstly, we present its application in robot-assisted play and therapy for children with autism. Secondly, we illustrate its use in human–robot interaction studies investigating the role of interaction kinesics and gestures. Lastly, we describe a study in the field of developmental robotics into computational architectures based on interaction histories for robot ontogeny. The three areas differ in the way as to how the robot is being operated and its role in social interaction scenarios. Each will be introduced briefly and examples of the results will be presented. Reflections on the specific design features of KASPAR that were important in these studies and lessons learnt from these studies concerning the design of humanoid robots for social interaction will also be discussed. An assessment of the robot in terms of utility of the design for human–robot interaction experiments concludes the paper.